ENERGI FUNKOT GRUP MUSIK PRONTAXAN DI TENGAH PERKEMBANGAN MUSIK INDIE DI INDONESIA - Sarinastiti, Tristania Berdieta (Universitas Negeri Makassar, 2023)
As original Indonesian music, Dangdut has an appeal that is quite popular with various groups of people. Along with the times, dangdut music has undergone interesting modifications by combining dangdut songs with electronic music called Funky Kota music (Funkot). The purpose of this study was to examine the process and role of the Prontaxan music group which brought Funkot music amidst the development of indie music in Indonesia. The research method uses a descriptive qualitative approach by collecting data through interviews, observation, and literature study. The results of the study show that Prontaxan has become one of the musical groups that have finally made genre no longer an aspect to judge someone through their taste in music. They make music as a unifier and entertainment for everyone who listens to it by using an indie music approach that is a victim of the remix creations they do. Then approach social media with content that is entertaining and in tune with young people and still seems peripheral to the slang language that is typical of Funkot music in its era